THE EFFECT OF TEPID SPONGE THERAPY ON REDUCING JOINT PAININ GOUT ARTHRITIS AT GENERAL CENDEKIA HUSADA CLINIC - Sulistyowati, Agus; Risti Puji Listari (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Gout arthritis is a form of inflammatory arthritis characterized by acute joint pain, swelling, and redness due to the accumulation of uric acid crystals in the joints. Non-pharmacological pain management, such as tepid sponge therapy (warm compresses), is starting to be considered as a safe and easy alternative. This therapy is thought to increase vasodilation, improve blood circulation, and help reduce pain levels. The aim was to determine the effect of tepid sponge therapy on reducing joint pain levels in gout arthritis patients. The method used was This study used a quantitative design with a pre-experimental one-group pretest-posttest approach. A total of 66 respondents diagnosed with gout arthritis and experiencing mild to moderate joint pain were selected using a purposive sampling technique. Pain levels were measured using a Numerical Rating Scale (NRS) before and after the intervention. Tepid sponge therapy was performed for 15 minutes on the painful joint area, twice a day for 3 consecutive days. Data analysis used a WilcoxonTest. Results: There was a significant reduction in pain levels after tepid sponge therapy. The results of wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of tepid sponge therapy on reducing joint pain in gouty arthritis. The conclusion is that tepid sponge therapy is effective in reducing joint pain in gouty arthritis sufferers. This intervention can be used as a simple and effective non-pharmacological treatment alternative to reduce joint pain.